2007
DOI: 10.1111/j.1469-8137.2007.02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin and dissemination of the pollen‐part mutated SC haplotype which confers self‐compatibility in apricot (Prunus armeniaca)

Abstract: Summary• In China, its centre of origin, apricot ( Prunus armeniaca ) is self-incompatible. However, most European cultivars are self-compatible. In most cases, selfcompatibility is a result of a loss-of-function mutation within the pollen gene ( SFB ) in the S C haplotype. Controlled pollinations performed in this work revealed that the cross 'Ceglédi óriás' ( S 8 S 9 ) × 'Ceglédi arany' ( S C S 9 ) set well, as expected, but the reciprocal cross did not.• Apricot S 8 , S 9 and S C haplotypes were analysed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(107 citation statements)
references
References 56 publications
8
94
2
Order By: Relevance
“…AprFBC8 F and R primers were used for discrimination of SFB C/8 allele (Halász et al, 2007). The size of the PCR products was compared with those previously published by other researchers (Vilanova et al, 2005;Halász et al, 2007Halász et al, , 2010.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AprFBC8 F and R primers were used for discrimination of SFB C/8 allele (Halász et al, 2007). The size of the PCR products was compared with those previously published by other researchers (Vilanova et al, 2005;Halász et al, 2007Halász et al, , 2010.…”
Section: Resultsmentioning
confidence: 99%
“…AprFBC8 F and R primers were used for discrimination of SFB C/8 allele (Halász et al, 2007). The size of the PCR products was compared with those previously published by other researchers (Vilanova et al, 2005;Halász et al, 2007Halász et al, , 2010. For S 8 and Sc alleles, although Vilanova et al (2005) and Halasz et al (2010) reported as 353 and also, Halasz et al (2013) reported as 355 bp, the hereby result obtained was 354 bp band size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this species a continuous decrease in heterozygosity is evident from the Central Asian gene centre to the Western European growing countries. This phenomenon was found to be linked to changes in the mating strategy (Halász et al, 2007;2010b), with self-compatibility arising putatively in the Eastern part of Turkey and then spreading rapidly into the Western regions, where it resulted in a heavy loss of genetic diversity (Pedryc et al, 2009). Selfcompatibility was also described in some Italian and Spanish almond cultivars (Godini, 1979;Socias i Company, 2004), but without any consequences for genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…According to Halasz et al, [2] there was absence of an S c allele in 44 of 51 apricot genotypes grown in Turkey and they were found to be self-incompatible. Halasz et al [31] also found that 60% of the varieties grown in Turkey are self-incompatible. In this study, 43 of the F 1 progenies had either S c S 1 or S c S 9 alleles, and they were self-compatible.…”
Section: Primersmentioning
confidence: 98%